2012
DOI: 10.1084/jem.20120239
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a genetic locus controlling bacteria-driven colitis and associated cancer through effects on innate inflammation

Abstract: A genetic locus acting in hematopoietic cells regulates cytokine expression and granulocyte recruitment to confer susceptibility in a Helicobacter hepaticus–induced model of innate colitis and associated cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 56 publications
(93 reference statements)
3
47
0
Order By: Relevance
“…In tissue, the IL-17 and IL-22 pathways were robustly induced (GM-CSF, IFN-γ, IL-6, IL-1β, KC, TNF-α). In the Rag2 −/− mouse these expression patterns point to phagocytes, innate lymphoid cells, or epithelial cells as possible sources (44)(45)(46)(47). Furthermore, the signals strongly connect neutrophils to the site of inflammation, confirming the previous demonstration based on histological evaluation (10).…”
Section: Quantitative Pcr Array-based Transcript Profiling Of Inflammsupporting
confidence: 82%
“…In tissue, the IL-17 and IL-22 pathways were robustly induced (GM-CSF, IFN-γ, IL-6, IL-1β, KC, TNF-α). In the Rag2 −/− mouse these expression patterns point to phagocytes, innate lymphoid cells, or epithelial cells as possible sources (44)(45)(46)(47). Furthermore, the signals strongly connect neutrophils to the site of inflammation, confirming the previous demonstration based on histological evaluation (10).…”
Section: Quantitative Pcr Array-based Transcript Profiling Of Inflammsupporting
confidence: 82%
“…With this Hiccs interval protection from H. hepaticus infection, innate immune responses of certain proinflammatory cytokines such as TNF, IL-1β, and INF-γ, were dampened[75]. This finding further confirms that some microRNAs are genetically destined to control inflammatory mediators.…”
Section: Introductionmentioning
confidence: 63%
“…Additionally, IL-22 keeps pathogenic microbiota at bay and its deficiency increases colitis 53 . Moreover, it has been shown that IL-22 can induce chemokines and various anti-bacterial peptides 51, 52, 54, 55 . In summary, IL-22 functions in maintaining the integrity of the epithelial barrier 51 , on the other hand, IL-22 is required for colitis development driven by Helicobacter in Rag -/- mice 55 .…”
Section: Intestinal Inflammation and Tumor Microenvironment: Differenmentioning
confidence: 99%